Вычислите (25 * ∛6 * √(6*∛6)) / ((⁴√36-1)(⁴√36+1))

Вычислите (25 * ∛6 * √(6*∛6)) / ((⁴√36-1)(⁴√36+1))
Гость
Ответ(ы) на вопрос:
Гость
[latex] = \frac{25* 6^{ \frac{1}{3} } * 6^{ \frac{1}{2}} * 6^{ \frac{1}{6} } }{ \sqrt{36} -1} = \frac{25*6}{5} = 30[/latex]
Гость
По действиям: 1) √(6 *∛6) =√(6 * 6^(¹/₃)) =√(6^(1+¹/₃)) =√(6^(⁴/₃)) = [6^(⁴/₃)]^(¹/₂) = 6^(⁴/₃ * ¹/₂) =     =6^(⁴/₆) 2) 25 * ∛6 * 6^(⁴/₆) = 25 * 6^(¹/₃) * 6^(⁴/₆) = 25 * 6^(¹/₃ ⁺ ⁴/₆) = 25 * 6^(²/₃ ⁺ ⁴/₆) =     = 25 * 6^(⁶/₆) = 25 * 6¹ = 150 3) (⁴√36 - 1)(⁴√36 +1) =(⁴√36)² - 1² = [36^(¹/₄)]² - 1 = 36^(¹/₂) - 1 =√36 - 1 =     =6-1 =5 4) 150/5=30 Ответ: 30.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы